Overlay Thickness of Flexible Pavement Analysis Using the Austroad 2010 Method and the Kenapave Program Case Study: CIPALI (Cikopo—Palimanan) Toll Road - Lau, Yansen Stevenson (Jurnal Teknik Sipil, 2019)
Toll roads have an important role on the economic development, therefore it is necessary to make road improvements to increase the road serviceability or minimum service standards (standar pelayanan minimal / SPM), as described in the Indonesian Government Regulation No. 34 of 2006 on roads. The CIPALI toll road has operated since 2015 and it connects Cikampek and Palimanan. Therefore, it is important to carry out a structural maintenance, in this case is by adding an overlay so that the pavement structure remains stable in supporting the repetition load which always increases over time. This study aims to analyze the overlay thickness using the AUSTROAD 2010 mechanistic procedure with the help of the CIRCLY and KENPAVE program, with a study area on the CIPALI toll road between kilometer 110 + 000 to kilometer 115 + 000.Referring to the results of the analysis, the overlay thickness calculated using the CIRCLY program requires a minimum thickness of 170 mm for the 2-layer model and 3-layer model in the direction towards Subang, and 160 mm for the 2-layer model and 150 mm for the 3-layer model in the direction toward Palimanan. The overlay thickness needed with an analysis using the linear-elastic KENLAYER program in the direction towards Palimanan is 140 mm for the 2-layer model and 100 mm for the 3-layer model, while the thickness of the overlay in the direction towards Subang is 160 mm for the 2-layer model and 130 mm for the 3-layer model. The overlay thickness needed with an analysis using the non-linear KENLAYER program in the direction towards is 120 mm for the 2-layer model and 80 mm for the 3-layer model, and for the direction toward Subang is 140 mm for the 2-layer model and 100 mm for the 3-layer model.